A GPU-based general numerical framework for plasma simulations in terms of microscopic kinetic equations with full collision terms - ZHANG, Junjie; ZHANG, Xin; PENG, Guoliang; REN, Zeping (Plasma science & technology, 2022)
We have proposed a general numerical framework for plasma simulations on graphics processing unit clusters based on microscopic kinetic equations with full collision terms. Our numerical algorithm consistently deals with both long-range (classical forces in the Vlasov term) and short-range (quantum processes in the collision term) interactions. Providing the relevant particle masses, charges and types (classical, fermionic or bosonic), as well as the external forces and the matrix elements (in the collisional integral), the algorithm consistently solves the coupled multi-particle kinetic equations. Currently, the framework is being tested and applied in the field of relativistic heavy-ion collisions; extensions to other plasma systems are straightforward. Our framework is a potential and competitive numerical platform for consistent plasma simulations.